Awaiting the European Court of Human Rights’ Judgment on Pushbacks on the Border with Belarus (Ius Novum, 2026)
This article reconstructs and critically assesses the evolution of the European Court of Human Rights’ case law on the contemporary ‘migration crisis’. It aims to predict the Court’s upcoming ruling on pushbacks on the border with Belarus. The Grand Chamber, the largest adjudicating formation, will render a judgment in three applications against Poland, Lithuania and Latvia. Two previous key cases – Khlaifia and Others v. Italy, and N.D. and N.T. v. Spain – were heard first by a seven-judge Chamber and then by the Grand Chamber. The judgments reached different conclusions: the Chambers found a violation of the provisions of the European Convention on Human Rights, while the Grand Chamber found no violation. The Grand Chamber’s rulings have reshaped the Convention’s legal standards, particularly regarding the prohibition of collective expulsions. These standards will be applied to the three cases concerning pushbacks on the border with Belarus.